Comparative Analysis of NIJ and NIST Methods for MicroSD Investigations: A Technopreneur Approach - Anwar, Nizirwan; Widodo, Agung Mulyo; Sekti, Binastya Anggara; Ulum, Muhamad Bahrul; Rahaman, Mosiur; Ariessanti, Hani Dewi (Aptisi Transactions On Technopreneurship (ATT), 2024)
This research aims to compare the performance of two forensic investigation methods, the National Institute of Justice (NIJ) and the National Institute of Standards and Technology (NIST), specifically for evidence analysis of MicroSD cards. MicroSD cards are frequently used as external storage in various digital devices, making them critical in digital forensic investigations. The study evaluates the effectiveness of these methods using tools such as Access Data FTK Imager and autopsy. The NIJ method enthis comparative passes detailed stages of preparation, collection, examination, analysis, and reporting, while the NIST method includes stages of collection, examination, analysis, and reporting. Results indicate that the NIJ method provides more comprehensive and detailed results, while the NIST method offers a faster investigation process. Additionally, tables and graphs illustrating performance metrics are included to substantiate the findings. This comparative analysis provides valuable insights for technopreneurs in optimizing digital forensic methods for better data integrity and efficiency, ultimately enhancing decision-making processes in technological entrepreneurship. Furthermore, this study aligns with the United Nations' Sustainable Development Goals (SDGs), particularly Goal 9: Industry, Innovation, and Infrastructure, by promoting innovative forensic methods that support the development of resilient infrastructure and foster innovation in the digital age. This study highlights the importance of effective forensic methods in supporting technopreneurial ventures.